Pancreas Injuries: Modern Approaches to Diagnosis and Surgical Treatment (Eurasian Medical Research Periodical, 2022)
Pregnant women may feel unwell during pregnancy if they have severe anemia; Increased chances of premature birth; There is a high risk of infection after childbirth. According to statistics, 40% of pregnant women suffer from anemia. The purpose of the study: To study the causes of anemia in pregnant women and the symptoms of anemia. The article provides information on the causes of anemia in pregnant women, their identification and symptoms that distinguish anemia from other diseases